FUNCTIONAL POTENTIAL OF UNCONVENTIONAL PLANT SOURCES - SANGLE, SANCHITA CHANDRAKANT; MANOHARAN, NIKITA; LIMGAOKAR, KIRTI; NIGAM, ANUKRITI (International Journal of Current Pharmaceutical Research, 2021)
Objective: Plant phenols are extensively studied, thanks to their many prophylactic (anti-tumoural, ulcer, inflammatory) and therapeutic effects. Their many antioxidants may protect against diabetes, cancer, autoimmune diseases. Our objective was to evaluate antioxidant and antimicrobial activities of our samples: Cocos nucifera (shell), Punica granatum (peel), Citrus limonum (rind), and Ocimum sanctum (stem); in conjugation with phytochemical analysis. Methods: The hydro-methanolic extracts of the selected plant parts were assessed for polyphenols. Antioxidant (ferric reducing power assay) and antibacterial (Kirby Bauer disc diffusion) assays were run for varying concentrations against-Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, and Salmonella typhi. Results: The results showed that the samples all contained polyphenols with high total phenolic activity in pomegranate and high antibacterial activity in coconut. A more comprehensive study could lead to their emphatic incorporation into mainstream medicine and pharmaceuticals–furnishing natural alternatives to their chemical counterparts. Conclusion: The present study concludes that hydro-methanolic extracts of the samples contain phytochemicals in high concentrations, conferring upon them promising antioxidant and antimicrobial activity.